Puumala orthohantavirus: prevalence, biology, disease, animal models and recent advances in therapeutics development and structural biology - Tscherne, Alina; Guardado-Calvo, Pablo; Clark, Jordan J.; Krause, Robert; Krammer, Florian (Frontiers in Immunology, 2025)
Puumala orthohantavirus (PUUV) is an emerging zoonotic virus that was first discovered in the Puumala region of Finland in the early 1980s and is the primary etiological agent of nephropathia epidemica (NE), a milder form of a life-threatening disease known as hemorrhagic fever with renal syndrome (HFRS). PUUV and other members of the Old World hantaviruses (OWHVs) predominantly circulate in rodents or insectivores across Eurasia, accounting for several thousand of reported HFRS cases every year (with many more unreported/misdiagnosed cases suspected). The rodent reservoir of PUUV is the common bank vole (Myodes (M.) glareolus), and transmission of the virus to humans occurs via inhalation of contagious aerosols and through contact with contaminated droppings or urine. Although PUUV is the subject of extensive research, due to its potential to cause severe disease outcomes in humans and its considerable economic and social impact, neither licensed vaccines nor specific antiviral treatments are available against PUUV. However, many important advancements have been made in terms of PUUV research over the last years. This included the elucidation of its glycoproteins, the discovery of broadly neutralizing hantavirus antibodies as therapeutic candidates and expanded research on the mRNA vaccine technology which will likely enable the development of strong PUUV vaccine candidates in the near future. Currently, there is still a lack of suitable animal models for the preclinical evaluation of experimental vaccines and antivirals, which hampers vaccine and antiviral development. Current attempts to decrease hantavirus-associated human infections rely primarily on prevention and countermeasures for rodent control, including reduced contact to droppings, saliva and urine, and disinfection of areas that are contaminated with rodent excreta. Here, we review these recent advances and other aspects including PUUV prevalence, virus biology, diagnosis and clinical features, and current animal models for vaccine and treatment development.